The Study Of The Contribution Of Indian Women To English Literature (Journal of Namibian Studies : History Politics Culture, 2023)
This study looks at the important contributions made by Indian women to English literature, emphasising their distinct viewpoints, life experiences, and storytelling customs. Notwithstanding cultural limitations and patriarchal conventions, Indian women have made noteworthy contributions to the development of literature. In order to demonstrate the variety of voices, topics, and narratives that Indian women authors have produced, the study examines significant literary works from a range of genres and historical periods. It explores the historical background and talks about the chances and difficulties Indian women authors like Sarojini Naidu, Kamala Das, and Arundhati Roy experienced. The study also looks at Indian women authors' involvement with socio-political realities and their thematic concerns, which include identity, gender, tradition, and modernity. The study examines the stylistic developments, narrative strategies, and thematic concerns of a few works by well-known Indian women writers. By recognising the wide spectrum of voices that have influenced English literature's growth, it seeks to contribute to a more inclusive and nuanced view of the genre.Top of Form